The effect of age and sex on selected hematologic and serum biochemical analytes in 4,804 elite endurance-trained sled dogs participating in the Iditarod Trail Sled Dog Race pre-race examination program - Connolly, Sara L. (PLoS One, 2020)
Endurance-trained sled dogs provide a unique translational model to characterize changes in hematologic and serum biochemical analytes due to the aging process. The primary objective of this study was to determine the effect of age and sex on specific hematologic and serum biochemical parameters in the endurance trained sled dog. Longitudinal and cross-sectional data were analyzed from 9,746 blood and serum samples from 4,804 dogs collected over 7 years as part of the Iditarod Trail Sled Dog Race pre-race examination program. Mixed models analysis was used for statistical analysis and P < 0.01 was considered significant. Dogs ranged from 1–12 years of age and 39% were female. Serum total calcium and phosphorus concentrations and white blood cell count decreased nonlinearly to asymptotic values by 6.6, 3.1, and 6.9 years of age, respectively, equivalent to estimated physiologic ages in human years of 44, 27, and 46 years. Serum glucose concentrations reached their lowest value at 7.8 years of age, equivalent to an estimated human physiologic age of 50 years, after which time the concentration increased. Serum globulin concentrations increased with age, but nonlinearly for females and linearly for males. Most sex-related differences were <5%; however, females had lower serum urea nitrogen (14.7%) and creatinine (7.3%) concentrations, lower serum alanine aminotransferase activity (16.6%), and higher serum total bilirubin concentration (12.8%) and platelet count (6.0%). The endurance-trained sled dog provides an excellent model to separate the physiologic effects of age from those of a sedentary lifestyle on hematologic and serum biochemical analytes.